GEOPHYSICALLY CONSTRAINED MANTLE MASS FLOWS AND THE 40AR BUDGET: A DEGASSED LOWER MANTLE? - Davies G.F. (My University, 1999)
It has been inferred previously that the lower mantle is much less degassed than the upper mantle, by about two orders of magnitude, based on estimates of the amount of 40Ar expected to have been generated during earth history. Such a gas-rich lower mantle would severely limit the permissible mass flow rate into the upper mantle. However a gas-rich lower mantle conflicts with evidence from refractory trace elements and their isotopes that most of the mantle has been processed, and with increasingly strong geophysical evidence for a large mass flow between the upper and lower mantle. Neither is it implied any longer by isotopic compositions of He, Ne and Ar from oceanic island basalts, which are nearly as radiogenic (within factors of 2-4) as those from mid-ocean ridge basalts. Here the budgets for mantle He, Ne and Ar are developed from geophysical and other geochemical constraints, but without assuming the total 40Ar content of the silicate earth to be known. These budgets permit the lower mantle to be only slightly less degassed than the upper mantle, though they show that the degree of lower mantle degassing inferred in this way depends strongly on poorly-constrained entrainment and degassing efficiencies of mantle plumes. A degassed lower mantle requires either (1) that the earth has 50% less 40K than is usually estimated, (2) that 40Ar is sequestered in the core, or (3) that 40Ar has been lost from the earth entirely. 40Ar in the core is hard to reconcile with chemical systematics. A small amount of argon loss from the earth during the late heavy meteorite bombardment is plausible, but 50% loss is difficult to justify at this stage. A 50% lower K/U ratio in the earth would remove the discrepancy and may not be outside the range of uncertainties. All three hypotheses need to be considered, and some combination of them may apply.
Keywords: NOBLE GASES; ISOTOPES; AR-40; MANTLE; DEGASSING